Empirical determination of solar proton access to the atmosphere: Impact on polar flight paths. Issue 7 (18th July 2013) - Neal, Jason J.; Rodger, Craig J.; Green, Janet C.
Abstract: [1] Violent expulsions on the Sun's surface release high energy solar protons that ultimately affect HF communication used by aircraft. The geomagnetic field screens the low altitude equatorial region, but these protons can access the atmosphere over the poles. The latitudes over which the solar protons can reach vary with geomagnetic indices such as Kp and Dst . In this study we use observations from low Earth orbit to determine the atmospheric access of solar protons and hence the flights paths most likely to be affected. Observations taken by up to six polar orbiting satellites during 15 solar proton events are analyzed. From this we determine 16, 850 proton rigidity cutoff estimates across three energy channels. Empirical fits are undertaken to estimate the most likely behavior of the cutoff dependence with geomagnetic activity. The changing Kp value is found to lead the variation in the cutoffs by ~3 h. We provide simple equations by which the geomagnetic latitude at which the protons impact the atmosphere can be determined from a given Kp or Dst value. The variation found in the cutoff with Kp is similar to that used in existing operational models, although we suggest that a ~1–2° equatorward shift in latitude would provide greater accuracy. We find that a Kp predictive model can provide additional warning to the variation in proton cutoffs. Hence, a prediction of the cutoff latitudes can be made ~3 h to as much as 7 h into the future, meeting suggested minimum planning times required by the aviation industry. Key Points: Polar HF communications are blacked out by solar protons, affecting aviation Geomagnetically varying polar region affected has been empirically determined Predictions can be made ~3‐7 hours into the future, meeting industry needs